Management of Trastuzumab Deruxtecan-related nausea and vomiting in real-world practice - Notini, Giulia; Naldini, Matteo Maria; Sica, Lorenzo; Viale, Giulia; Rognone, Alessia; Zambelli, Stefania; Zucchinelli, Patrizia; Piras, Marta; Bosi, Carlo; Mariani, Marco; Aldrighetti, Daniela; Bianchini, Giampaolo; et al. (Frontiers in Oncology, 2024)
Background: Nausea and vomi)ng are common side effects of Trastuzumab Deruxtecan (T-DXd), but guidelines for op)mal management were not ini)ally available. This retrospec)ve single-centre study aimed at evalua)ng the efficacy of two an)eme)c regimens in pa)ents receiving T-DXd.Methods: Data from metasta)c breast cancer pa)ents receiving T-DXd were collected. Two groups were defined: pa)ents treated with 5-HT3 receptor antagonists (RA) +/-dexamethasone (5-HT3-group), and pa)ents treated with a fixed oral combina)on of netupitant (NK1RA) and palonosetron +/-dexamethasone (NK1-group). Physicians preferen)ally offered the NK1 regimen to pa)ents at higher risk of nausea and vomi)ng based on internal recommenda)ons. Only nausea and vomi)ng during cycles 1 and 2 were considered. Comparisons of nausea and vomi)ng by an)eme)c prophylaxis group were assessed using chisquare.Results: Fijy-three pa)ents were included in the analysis. At cycle 1, 72% and 28% of pa)ents received the 5-HT3 and NK1 prophylaxis, respec)vely. Overall, 58% reported nausea, with no differences between groups (58% vs 60%; p=0.832), but with a trend for lower grade in the NK1 group (33.3% G1; 26.7% G2) compared to the 5-HT3 group (23.7% G1; 31.6% G2; 2.6% G3). Vomi)ng was reported by 21% and 0% of pa)ents in the 5-HT3 and the NK1 group, respec)vely (p=0.054). Among the 15 pa)ents in the 5-HT3 group with nausea at cycle 1 who escalated to NK1 at cycle 2, nausea decreased from 100% to 53% (p=0.022), and vomi)ng decreased from 47% to 13% (p=0.046).The NK1 regimen improved vomi)ng control at cycle 1 and, when introduced at cycle 2, significantly improved both nausea and vomi)ng. The biased NK1 selec)on for higher-risk pa)ents may have dampened the differences between groups at cycle 1. These findings support enhanced control of T-DXd-related nausea and vomi)ng with NK1RA.